Method for improving efficiency of replacing cadmium in high-concentration cadmium solution by ultrasonic low-temperature aluminum powder
By ultrasonic modification of aluminum powder, the oxide film was removed, and the surface-modified aluminum powder was used to replace the high-concentration cadmium solution at low temperature, which solved the problem of low cadmium replacement efficiency and safety hazards of aluminum powder at high temperatures, and achieved efficient cadmium Replacement effect.
Patent Information
- Application Number
- CN202411220504.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, the cadmium replacement rate when aluminum powder replaces high concentration cadmium solution at high temperatures is low, and there are safety hazards, such as volatility of acidic harmful gases and fire explosion risks.
By ultrasonic modification pretreatment of aluminum powder in acidic solution, remove the aluminum oxide film on the surface of aluminum powder, change the surface structure of aluminum powder, use surface modified aluminum powder as cadmium replacement agent, and perform ultrasonic cadmium replacement under low temperature conditions, accurately Control the pretreatment time and pH value to improve cadmium replacement efficiency.
It has achieved efficient replacement of cadmium in high-concentration cadmium solution under low temperature and low aluminum powder consumption conditions, and the cadmium replacement rate reaches more than 95%, reducing safety hazards and heat release of aluminum powder.
Smart Images

Figure HDA0005022877600000011 
Figure HDA0005022877600000012 
Figure HDA0005022877600000021
Abstract
Description
Technical Field
[0001] The invention relates to a method for improving the replacement efficiency of cadmium in a high-concentration cadmium solution by ultrasonic low-temperature aluminum powder, and belongs to the technical field of forging manufacturing. Background Art
[0002] During the lead smelting process, 80-90% of the cadmium in the lead raw materials is enriched in the smoke and soot, resulting in the cadmium content in the smoke and soot being as high as 15%-30%, affecting the normal production of the lead smelting system. At present, the main process for enriching cadmium from cadmium-containing soot is leaching-replacement, which is to use acid leaching or water leaching to convert the cadmium compounds in the soot into cadmium sulfate and enter the leaching solution, and then replace the cadmium in the leaching solution with a replacement agent.
[0003] The potential difference (+1.26V) between aluminum powder (Al) and cadmium is greater than that of traditional replacement agents such as zinc powder and iron powder. Using aluminum as a replacement agent for cadmium can theoretically achieve a good replacement effect. However, in the prior art, the process of aluminum powder replacing cadmium is carried out at a high temperature of 103-105°C and for a long time of 40-70 minutes, and its cadmium replacement rate is only 89%. In addition, the high-temperature aluminum powder replacement of cadmium is prone to volatilization of acidic harmful gases, which will bring hidden dangers such as liquid scalds and acid mist injuries, and necessary protective measures must be taken. Aluminum powder will quickly release a large amount of heat under high temperature conditions in the solution, causing the reaction environment temperature and pressure to rise sharply and generate a large amount of dangerous gas-hydrogen, which is easy to cause fire and explosion accidents, posing a huge safety hazard to the operating environment.
[0004] The applicant discovered in the study of ultrasonic low-temperature aluminum powder replacement method that directly adding aluminum powder (25g / L) to a cadmium solution with a cadmium ion concentration of 5g / L and introducing ultrasonic waves can improve the replacement effect of the aluminum powder, and the cadmium replacement rate is as high as 95.08%; however, when the cadmium ion concentration in the cadmium solution is as high as 10-30g / L, even with the introduction of ultrasonic waves, the cadmium replacement rate is no higher than 83%, and its cadmium replacement rate decreases as the cadmium ion concentration increases. Summary of the invention
[0005] In view of the problem that the cadmium replacement rate is still low even when ultrasound is introduced in the current technical solution of replacing high-concentration cadmium (10-30g / L) with aluminum powder, the present invention proposes a method for improving the replacement efficiency of cadmium in a high-concentration cadmium solution by ultrasonic low-temperature aluminum powder. The present invention strictly controls the ultrasonic pretreatment time and pH value of aluminum powder modification to remove the aluminum oxide film on the surface of the aluminum powder and change the surface structure of the aluminum powder. The surface-modified aluminum powder is used as a cadmium replacement agent, which can achieve efficient replacement of cadmium in a high-concentration cadmium solution under low temperature and low aluminum powder consumption conditions, thereby improving the cadmium replacement efficiency (cadmium replacement rate reaches more than 95%).
[0006] A method for improving the replacement efficiency of cadmium in a high-concentration cadmium solution by ultrasonic low-temperature aluminum powder, the specific steps are as follows:
[0007] (1) adding aluminum powder to an acidic solution, and performing ultrasonic modification pretreatment for 60 to 240 seconds at a temperature of 20 to 70° C. and a pH value of 0.5 to 3 to obtain surface-modified aluminum powder; the ultrasonic power density is 100 to 500 W / L;
[0008] (2) adding the surface-modified aluminum powder to a high-concentration cadmium solution, performing ultrasonic cadmium replacement at room temperature to obtain high-cadmium slag and a replacement liquid, and estimating the cadmium replacement rate through a cadmium replacement rate function; the cadmium content in the high-concentration cadmium solution is 10 to 30 g / L.
[0009] Preferably, the acidic solution in step (1) is a sulfuric acid solution.
[0010] Preferably, the solid-to-liquid ratio g:L of the surface-modified aluminum powder and the high-concentration cadmium solution in step (2) is 8 to 20:1.
[0011] Preferably, in step (2), the ultrasonic power density is 100 to 300 W / L, and the cadmium replacement time is 30 to 90 min.
[0012] The replacement rate function of cadmium in step (2) is:
[0013] M=88.43-0.009x 1 +0.85x 2 +0.002x 3 +0.15x 4 -0.005x 5
[0014] Where, M is the cadmium replacement rate, unit is %; x 1 x is the ultrasonic modification pretreatment time of aluminum powder, in seconds; 2 is pH value; x 3 is the power of ultrasound, in W / L; x 4 is the modification pretreatment temperature, in °C; x 5 is the cadmium content, in g / L.
[0015] The present invention improves the efficiency of ultrasonic low-temperature aluminum powder in replacing cadmium in a high-concentration cadmium solution by: (1) accurately controlling the pretreatment time to achieve rapid electron release of the surface-modified aluminum powder, so that the high-concentration cadmium solution maintains a low-potential, high-reducing atmosphere: adding surface-modified aluminum powder (ultrasonic modification treatment for 360 seconds) to the high-concentration cadmium solution, since the internal aluminum continuously releases electrons without being restricted by the aluminum oxide film, the potential of the high-concentration cadmium solution is rapidly reduced ( Figure 1); When unmodified aluminum powder is added to a high concentration cadmium solution, the potential of the high concentration cadmium solution remains basically unchanged within 240 seconds after the start of the reaction because the aluminum oxide film makes it difficult for electrons to escape. After the time is extended to 600 seconds, it slowly decreases, but it still cannot reach the level of surface-modified aluminum powder; therefore, the ultrasonic modification time is controlled to be 60 to 600 seconds, preferably 60 to 240 seconds; (2) Precisely control the pretreatment pH value to achieve effective corrosion of the aluminum oxide film by the acidic solution, only changing the surface structure of the aluminum powder (fluffy and not dense), and not destroying the internal aluminum powder structure: if the pH of the acidic solution is too low, the aluminum oxide film will be corroded while the aluminum powder will also react with the acid, reducing the effective utilization rate of the aluminum powder; if the pH of the acidic solution is high, the removal rate of the aluminum oxide film is low, and it is easy to undergo hydration reaction to form aluminum hydrate, which makes the aluminum powder easy to agglomerate and reduces the replacement effect of the aluminum powder. Therefore, the pretreatment pH is controlled to be 0.5 to 5, preferably 1 to 2.
[0016] The beneficial effects of the present invention are:
[0017] The invention strictly controls the ultrasonic pretreatment time and pH value of aluminum powder modification to remove the aluminum oxide film on the surface of the aluminum powder and change the surface structure of the aluminum powder. The surface-modified aluminum powder is used as a cadmium replacement agent to achieve efficient replacement of cadmium in a high-concentration cadmium solution under low temperature and low aluminum powder consumption conditions, thereby improving the cadmium replacement efficiency (the cadmium replacement rate reaches more than 95%). BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The OCP-time curves of aluminum powder without surface modification and aluminum powder with surface modification (ultrasonic modification for 360 seconds) are shown;
[0019] Figure 2 The SEM images of aluminum powder without surface modification and aluminum powder with surface modification (ultrasonic modification treatment for 360s) are shown;
[0020] Figure 3 This is the SEM characterization of the solid obtained after 5 minutes of replacement of the unsurface-modified aluminum powder and the surface-modified aluminum powder in Example 1. DETAILED DESCRIPTION
[0021] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0022] Comparative Example 1: Aluminum powder without surface modification was added to a high-concentration cadmium solution (cadmium content was 20 g / L), the solid-liquid ratio of the aluminum powder to the high-concentration cadmium solution was 15:1, and ultrasonic cadmium replacement was performed at room temperature for 60 min (ultrasonic power density was 200 W / L) to obtain high-cadmium slag and replaced liquid;
[0023] The ICP method showed that the cadmium ion content in the liquid after replacement was 4.97 g / L, and the cadmium replacement rate was calculated to be 75.13%.
[0024] Example 1: A method for improving the efficiency of replacing cadmium in a high-concentration cadmium solution by ultrasonic low-temperature aluminum powder, the specific steps are as follows:
[0025] (1) adding aluminum powder to a sulfuric acid solution, and performing ultrasonic modification pretreatment for 180 seconds at a temperature of 60° C. and a pH value of 1.5 to obtain surface-modified aluminum powder; the ultrasonic power density is 200 W / L;
[0026] (2) Surface-modified aluminum powder was added to a high-concentration cadmium solution (cadmium content was 20 g / L), the solid-liquid ratio of the surface-modified aluminum powder to the high-concentration cadmium solution was 15:1, and ultrasonic cadmium replacement was performed at room temperature for 60 min (ultrasonic power density was 200 W / L) to obtain high-cadmium slag and replaced liquid. The cadmium replacement rate was estimated to be 97.39% through the cadmium replacement rate function; the cadmium replacement rate function is:
[0027] M=88.43-0.009x 1 +0.85x 2 +0.002x 3 +0.15x 4 -0.005x 5
[0028] Where, M is the cadmium replacement rate, unit is %; x 1 x is the ultrasonic modification pretreatment time of aluminum powder, in seconds; 2 is pH value; x 3 is the power of ultrasound, in W / L; x 4 is the modification pretreatment temperature, in °C; x 5 is the cadmium content, in g / L.
[0029] The ICP method was used to detect that the cadmium ion content in the liquid after replacement was 0.49 g / L, and the cadmium replacement rate was calculated to be 97.53%, and the estimated cadmium replacement rate was 97.39%, with an error of 0.14%. Compared with the aluminum powder without surface modification treatment in Comparative Example 1, the cadmium replacement rate of this embodiment was increased by 22.4%.
[0030] Compared with the aluminum powder of Comparative Example 1 which has not been subjected to surface modification treatment, Figure 2 As shown, the aluminum oxide film on the surface of the aluminum powder without surface modification in Comparative Example 1 has a dense structure and a clear outline ( Figure 2 a); The aluminum powder modified in this embodiment has rough edges and severe corrosion ( Figure 2 b);
[0031] Compared with the aluminum powder of Comparative Example 1 which has not been subjected to surface modification treatment, Figure 3 As shown, the aluminum powder of Comparative Example 1 without surface modification generates more hydroxides because the aluminum oxide film is not removed and the surface is dense, resulting in obvious agglomeration ( Figure 3 a); and in the present embodiment, during the replacement process of the modified aluminum powder in the high concentration cadmium solution, the surface modified aluminum powder is well dispersed and does not agglomerate (3b), and the replacement reaction is easy to occur, thereby improving the cadmium replacement rate.
[0032] Comparative Example 2: Aluminum powder without surface modification was added to a high-concentration cadmium solution (cadmium content was 30 g / L), the solid-liquid ratio of the aluminum powder to the high-concentration cadmium solution was 15:1, and ultrasonic cadmium replacement was performed at room temperature for 60 min (ultrasonic power density was 200 W / L) to obtain high-cadmium slag and replaced liquid;
[0033] The ICP method showed that the cadmium ion content in the liquid after replacement was 11.35 g / L, and the cadmium replacement rate was calculated to be 62.17%.
[0034] Example 2: A method for improving the efficiency of ultrasonic low-temperature aluminum powder replacing cadmium in a high-concentration cadmium solution, the specific steps are as follows:
[0035] (1) adding aluminum powder to a sulfuric acid solution, and performing ultrasonic modification pretreatment for 240 seconds at a temperature of 30° C. and a pH value of 0.5 to obtain surface-modified aluminum powder; the ultrasonic power density is 500 W / L;
[0036] (2) Surface-modified aluminum powder was added to a high-concentration cadmium solution (cadmium content was 30 g / L), the solid-liquid ratio of the surface-modified aluminum powder to the high-concentration cadmium solution was 15:1, and ultrasonic cadmium replacement was performed at room temperature for 60 min (ultrasonic power density was 200 W / L) to obtain high-cadmium slag and replaced liquid. The cadmium replacement rate was estimated to be 92.05% through the cadmium replacement rate function; the cadmium replacement rate function is:
[0037] M=88.43-0.009x 1 +0.85x 2 +0.002x 3 +0.15x 4 -0.005x 5
[0038] Where, M is the cadmium replacement rate, unit is %; x 1 x is the ultrasonic modification pretreatment time of aluminum powder, in seconds; 2 is pH value; x 3 is the power of ultrasound, in W / L; x 4 is the modification pretreatment temperature, in °C; x 5is the cadmium content, in g / L.
[0039] The cadmium ion content in the liquid after replacement was 2.06 g / L detected by the ICP method, and the cadmium replacement rate was calculated to be 93.03%, and the estimated cadmium replacement rate was 92.05%, with an error of 0.98%. Compared with the aluminum powder without surface modification in comparative example 1, the cadmium replacement rate of this embodiment was increased by 30.86%.
[0040] Comparative Example 3: Aluminum powder without surface modification was added to a high-concentration cadmium solution (cadmium content was 10 g / L), the solid-liquid ratio of the aluminum powder to the high-concentration cadmium solution was 15:1, and ultrasonic cadmium replacement was performed at room temperature for 60 min (ultrasonic power density was 200 W / L) to obtain high-cadmium slag and replaced liquid;
[0041] The ICP method showed that the cadmium ion content in the liquid after replacement was 1.75 g / L, and the cadmium replacement rate was calculated to be 82.54%.
[0042] Example 3: A method for improving the efficiency of ultrasonic low-temperature aluminum powder replacing cadmium in a high-concentration cadmium solution, the specific steps are as follows:
[0043] (1) adding aluminum powder to a sulfuric acid solution, and performing ultrasonic modification pretreatment for 60 seconds at a temperature of 50° C. and a pH value of 1.5 to obtain surface-modified aluminum powder; the ultrasonic power density is 100 W / L;
[0044] (2) Surface-modified aluminum powder was added to a high-concentration cadmium solution (cadmium content was 10 g / L), the solid-liquid ratio of the surface-modified aluminum powder to the high-concentration cadmium solution was 15:1, and ultrasonic cadmium replacement was performed at room temperature for 60 min (ultrasonic power density was 200 W / L) to obtain high-cadmium slag and replaced liquid. The cadmium replacement rate was estimated to be 96.82% through the cadmium replacement rate function; the cadmium replacement rate function is:
[0045] M=88.43-0.009x 1 +0.85x 2 +0.002x 3 +0.15x 4 -0.005x 5
[0046] Where, M is the cadmium replacement rate, unit is %; x 1 x is the ultrasonic modification pretreatment time of aluminum powder, in seconds; 2 is pH value; x 3 is the power of ultrasound, in W / L; x 4 is the modification pretreatment temperature, in °C; x 5 is the cadmium content, in g / L.
[0047] The cadmium ion content in the liquid after replacement was 0.31 g / L detected by the ICP method, and the cadmium replacement rate was calculated to be 96.94%, and the estimated cadmium replacement rate was 96.82%, with an error of 0.12%. Compared with the aluminum powder without surface modification in comparative example 1, the cadmium replacement rate of this embodiment was increased by 14.4%.
[0048] Comparative Example 4: Aluminum powder without surface modification was added to a high-concentration cadmium solution (cadmium content was 25 g / L), the solid-liquid ratio of the aluminum powder to the high-concentration cadmium solution was 12:1, and ultrasonic cadmium replacement was performed at room temperature for 60 min (ultrasonic power density was 200 W / L) to obtain high-cadmium slag and replaced liquid;
[0049] The ICP method showed that the cadmium ion content in the liquid after replacement was 5.21 g / L, and the cadmium replacement rate was calculated to be 79.07%.
[0050] Example 4: A method for improving the efficiency of ultrasonic low-temperature aluminum powder replacing cadmium in a high-concentration cadmium solution, the specific steps are as follows:
[0051] (1) adding aluminum powder to a sulfuric acid solution, and performing ultrasonic modification pretreatment for 60 seconds at a temperature of 70° C. and a pH value of 1.5 to obtain surface-modified aluminum powder; the ultrasonic power density is 400 W / L;
[0052] (2) Surface-modified aluminum powder was added to a high-concentration cadmium solution (cadmium content was 25 g / L), the solid-liquid ratio of the surface-modified aluminum powder to the high-concentration cadmium solution was 12:1, and ultrasonic cadmium replacement was performed at room temperature for 60 min (ultrasonic power density was 200 W / L) to obtain high-cadmium slag and replaced liquid. The cadmium replacement rate was estimated to be 100.34% through the cadmium replacement rate function; the cadmium replacement rate function is:
[0053] M=88.43-0.009x 1 +0.85x 2 +0.002x 3 +0.15x 4 -0.005x 5
[0054] Where, M is the cadmium replacement rate, unit is %; x 1 x is the ultrasonic modification pretreatment time of aluminum powder, in seconds; 2 is pH value; x 3 is the power of ultrasound, in W / L; x 4 is the modification pretreatment temperature, in °C; x 5 is the cadmium content, in g / L.
[0055] The cadmium ion content in the liquid after replacement was 0.21 g / L by ICP method, and the cadmium replacement rate was calculated to be 99.07%, and the estimated cadmium replacement rate was 100.34%, with an error of 1.27%. Compared with the aluminum powder of comparative example 4 without surface modification, the cadmium replacement rate of this embodiment was increased by 20%.
[0056] Comparative Example 5: A method for replacing cadmium in a high-concentration cadmium solution with low-temperature aluminum powder, wherein the specific steps are as follows:
[0057] The aluminum powder without surface modification is added into a high concentration cadmium solution (cadmium content is 25 g / L), wherein the solid-liquid ratio g:L of the aluminum powder to the high concentration cadmium solution is 18:1, and ultrasonic cadmium replacement is performed at room temperature for 60 min (ultrasonic power density is 200 W / L) to obtain high cadmium slag and replacement liquid;
[0058] The ICP method showed that the cadmium ion content in the liquid after replacement was 4.73 g / L, and the cadmium replacement rate was calculated to be 76.37%.
[0059] Comparative Example 6: A method for replacing cadmium in a high-concentration cadmium solution with low-temperature aluminum powder, wherein the specific steps are as follows:
[0060] (1) placing aluminum powder in a ball mill filled with stainless steel balls and ball milling for 60 minutes to obtain ball milled surface-modified aluminum powder;
[0061] (2) adding the surface-modified aluminum powder by ball milling into a high-concentration cadmium solution (cadmium content of 25 g / L), wherein the solid-to-liquid ratio of the aluminum powder to the high-concentration cadmium solution is 18:1, and performing ultrasonic cadmium replacement for 60 min (ultrasonic power density of 200 W / L) at room temperature to obtain high-cadmium slag and a replaced liquid;
[0062] The ICP method showed that the cadmium ion content in the liquid after replacement was 5.21 g / L, and the cadmium replacement rate was calculated to be 79.05%.
[0063] Comparative Example 7: A method for replacing cadmium in a high-concentration cadmium solution with low-temperature aluminum powder, the specific steps are as follows:
[0064] (1) Through aluminum and Fe 2+ The surface modified aluminum powder is obtained by surface doping method by depositing iron on the aluminum surface by reaction method;
[0065] (2) adding the surface-modified aluminum powder by the surface doping method to a high-concentration cadmium solution (cadmium content of 25 g / L), wherein the solid-liquid ratio g:L of the aluminum powder to the high-concentration cadmium solution is 18:1, and performing ultrasonic cadmium replacement for 60 min (ultrasonic power density of 200 W / L) at room temperature to obtain high-cadmium slag and a replaced liquid;
[0066] The ICP method showed that the cadmium ion content in the liquid after replacement was 4.47 g / L, and the cadmium replacement rate was calculated to be 82.14%.
[0067] Example 5: A method for improving the efficiency of ultrasonic low-temperature aluminum powder replacing cadmium in a high-concentration cadmium solution, the specific steps are as follows:
[0068] (1) adding aluminum powder to a sulfuric acid solution, and performing ultrasonic modification pretreatment for 200 seconds at a temperature of 20° C. and a pH value of 2.0 to obtain surface-modified aluminum powder; the ultrasonic power density is 300 W / L;
[0069] (2) Surface-modified aluminum powder was added to a high-concentration cadmium solution (cadmium content was 25 g / L), the solid-liquid ratio of the surface-modified aluminum powder to the high-concentration cadmium solution was 18:1, and ultrasonic cadmium replacement was performed at room temperature for 60 min (ultrasonic power density was 200 W / L) to obtain high-cadmium slag and replaced liquid. The cadmium replacement rate was estimated to be 91.81% through the cadmium replacement rate function; the cadmium replacement rate function is:
[0070] M=88.43-0.009x 1 +0.85x 2 +0.002x 3 +0.15x 4 -0.005x 5
[0071] Where, M is the cadmium replacement rate, unit is %; x 1 x is the ultrasonic modification pretreatment time of aluminum powder, in seconds; 2 is pH value; x 3 is the power of ultrasound, in W / L; x 4 is the modification pretreatment temperature, in °C; x 5 is the cadmium content, in g / L.
[0072] According to the ICP method, the cadmium ion content in the liquid after replacement is 2.06 g / L, the cadmium replacement rate is calculated to be 91.75%, the estimated cadmium replacement rate is 91.81%, and the error is 0.06%; compared with the aluminum powder of comparative example 5 without surface modification, the cadmium replacement rate of this embodiment is increased by 15.38%; compared with the aluminum powder of comparative example 6 surface modified by ball milling method, the cadmium replacement rate of this embodiment is increased by 12.76%; compared with the aluminum powder of comparative example 7 surface modified by surface doping method, the cadmium replacement rate of this embodiment is increased by 9.61%.
[0073] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A method for improving the efficiency of ultrasonic low-temperature aluminum powder replacing cadmium in a high-concentration cadmium solution, characterized in that: The specific steps are as follows: (1) adding aluminum powder to an acidic solution, and performing ultrasonic modification pretreatment for 60 to 240 seconds at a temperature of 20 to 70° C. and a pH value of 0.5 to 3 to obtain surface-modified aluminum powder; the ultrasonic power density is 100 to 500 W / L; (2) adding the surface-modified aluminum powder to a high-concentration cadmium solution, performing ultrasonic cadmium replacement at room temperature to obtain high-cadmium slag and a replacement liquid, and estimating the cadmium replacement rate through a cadmium replacement rate function; the cadmium content in the high-concentration cadmium solution is 10 to 30 g / L.
2. The method for improving the replacement efficiency of cadmium in a high-concentration cadmium solution by ultrasonic low-temperature aluminum powder according to claim 1, characterized in that: The acidic solution in step (1) is a sulfuric acid solution.
3. The method for improving the replacement efficiency of cadmium in a high-concentration cadmium solution by ultrasonic low-temperature aluminum powder according to claim 1, characterized in that: In step (2), the solid-to-liquid ratio g:L of the surface-modified aluminum powder and the high-concentration cadmium solution is 8 to 20:
1.
4. The method for improving the replacement efficiency of cadmium in a high-concentration cadmium solution by ultrasonic low-temperature aluminum powder according to claim 1, characterized in that: The ultrasonic power density in step (2) is 100 to 300 W / L, and the cadmium replacement time is 30 to 90 min.
5. The method for improving the replacement efficiency of cadmium in a high-concentration cadmium solution by ultrasonic low-temperature aluminum powder according to claim 1, characterized in that: The substitution rate function of cadmium in step (2) is: M=88.43-0.009x1+0.85x2+0.002x3+0.15x4-0.005x5 Wherein, M is the cadmium replacement rate, in %; x1 is the ultrasonic modification pretreatment time of aluminum powder, in s; x2 is the pH value; x3 is the ultrasonic power, in W / L; x4 is the modification pretreatment temperature, in ℃; x5 is the cadmium content, in g / L.
Citation Information
Cited By
Interface regulation and control method for ultrasonic enhanced replacement in ultrahigh-concentration cadmium solution
CN122428143A
